Effects of respiratory exercises in sleep bruxism and associated obstructive sleep apnea: a double-blind, placebo-controlled randomized clinical trial - Bianca Lopes Cavalcante-Leao; André Luís Porporatti; Rosa Cíntia Felicio Adriano; Rosane Sampaio Santos; Maria Isabel Vanelli; Isabella Perez; Cristiano Miranda de Araújo; José Stechman-Neto; Bianca Simone Zeigelboim (Medical Journals Sweden, 2024)
Purpose: The aim of this study is to assess the effects of respiratory exercises (inspiratory and expiratory) in individuals with sleep bruxism (SB) and associated obstructive sleep apnea (OSA). Methods: This is a double-blind, placebo-controlled randomized clinical trial including individuals with SB and associated respiratory events in OSA. Respiratory physical therapy was performed using inspiratory (Threshold® IMT), expiratory (Threshold® PEP) muscle training, and compared with a placebo group. A total of 30 daily respiratory cycles (inspiration and expiration) were performed five times a week for 12 weeks. Individuals were reassessed at two times, at baseline (T1) and after 12 weeks of training (T2) by means of the Pittsburgh Sleep Quality Index and Polysomnography. Results: Awakening was significantly different (p ≤ 0.05) between the inspiratory group and placebo 12 weeks after respiratory physical therapy. The number of contractions of the masseter muscle differed between the inspiratory, expiratory, and placebo groups (p ≤ 0.05). Conclusion: Respiratory physical therapy for OSA improved awaking levels in 80 and 67% of the number of masseter muscle contractions, when compared to placebo. Trial registration: Brazilian Registry of Clinical Trials (No. RBR-9F6JKM)